Excelling at youth level in competitive track and field athletics is not a prerequisite for later success - Kearney, P. E.; Hayes, P. R. (Journal of Sports Sciences, 2018)
Enhancing our understanding of athlete development would be valuable for coaches, parents and administrators to set realistic performance expectations and to advance youth sport policy. To this end, a database of track and field performances was examined. Records of 134,313 performances by athletes aged between 12 and 35 years in sprinting, throwing, jumping and middle distance events were analysed. Results revealed that a minority (Male, 9%; Female, 13%) of top 20 ranked senior athletes were also ranked in the top 20 at Under 13 (U13). These results were supported by the finding that a minority of athletes retained their top 20 ranking at subsequent age grades (36.3% U13-U15; 23% U13-U17; 13% U13-U20; 43.3% U15-U17; 22.1% U15-U20; 41.8% U17-U20). By U20, less than 30% of athletes who had been ranked in the top 20 at U13 were still listed on the national rankings. Examining a broader sample of athletes revealed weak to moderate correlations between performances at different age grades until at least Under 17-Under 20. These findings reinforce the message that excelling at youth level in competitive athletics is not a prerequisite for senior success.